GROWTH OPPORTUNITY DAN FIRM SIZE TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING PERIODE 2018-2021 - Khosnul Khotimah; Ika Wahyuni; Ida Subaida (Fakultas Ekonomi dan Bisnis, 2023)
Economic igrowth iis ia imeasure iof ia icountry's iprogress ican ibe imeasured iby ithe iproduction isector. iFood iand ibeverage icompany igrowing irapidly iat ithis itime, ibecause iit iis ione iof ithe ineeds iof isociety iin igeneral, ithe imore iwidespread iexpansion iis iexpected ito ideliver icontribution ito isociety iand ithe icompany.. iThe ipurpose iof ithis iresearch iis ito i ianalyze iand itest ithe iinfluenceGrowth iOpportunity iandFirm isize iAgainst iCompany iValue iin iFood iand iBeverage iSub-Sector iCompanies iListed ion ithe iIndonesia iStock iExchange iWith iProfitability ias ian iIntervening iVariable ifor ithe i2018-2021 iPeriod. iThe ipopulation iin ithis istudy iare ifood iand ibeverage isub-sector icompanies ilisted ion ithe iIndonesia iStock iExchange ifor ithe i2018-2021 iperiod. iThe isampling itechnique iused iwas ipurposive isampling. iData ianalysis iand ihypothesis itesting iin ithis istudy iused ithe iStructural iEquation iModel i- iPartial iLeast iSquare i(PLS-SEM). The iresults iof ithe idirect iinfluence ihypothesis itest iusing ithe iSmart iPLS i3.0 iapplication, ishow ithatGrowth iOpportunity ipositive isignificant ieffect ion iProfitability,Firm isize ipositive ibut inot isignificant ieffect ion iProfitability,Growth iopportunity inegative ibut inot isignificant ieffect ion ifirm ivalue,Firm isize ihas ia isignificant ipositive ieffect ion ifirm ivalue, iProfitability ihas ia isignificant ipositive ieffect ion ifirm ivalue,Growth iopportunity ipositive isignificant ieffect ion ifirm ivalue ithrough iprofitability,Firm isize ihas ia ipositive ibut inot isignificant ieffect ion icompany ivalue ithrough iprofitability.